Phytochemistry, health benefits, and food applications of sea buckthorn (Hippophae rhamnoides L.): A comprehensive review - Wang, Zhen; Zhao, Fenglan; Wei, Panpan; Chai, Xiaoyun; Hou, Guige; Meng, Qingguo (Frontiers in Nutrition, 2022)
Sea buckthorn (Hippophae rhamnoides L.), an ancient miraculous plant, is of great interest because of its tenacity, richness in nutritional active substances and biological activity. Sea buckthorn is a deciduous shrub or tree of the genus Hippophae in the family Elaeagnaceae. It is a pioneer tree species for soil improvement, wind and sand control, and soil and water conservation. Sea buckthorn contains many nutritional active components such as vitamins, carotenoids, polyphenols, fatty acids, and phytosterols. Moreover, sea buckthorn has many health benefits. such as such as antioxidant, anticancer, anti-hyperlipidemic, anti-obesity, anti-inflammatory, antimicrobial, antiviral, dermatological, neuroprotective and hepatoprotective activities. Sea buckthorn not only has great medicinal and therapeutic potential, but also is a promising economic plant. The potential of sea buckthorn in the human food industry has attracted the research interest of researchers and producers. The present review mainly summarizes the phytochemistry, nutrients, health benefits, and food applications of sea buckthorn. Overall, sea buckthorn is a dietary source of bioactive ingredients with the potential to be developed into functional foods or dietary supplements for the prevention and treatment of certain chronic diseases, which deserves further research.